A interiorização da capital pela Estrada de Ferro Sul do Espírito Santo - Quintão, Leandro do Carmo (2008)
The objective of this dissertation of Social History of the Political Relationships is to discuss the relevance of Espírito Saint South Railroad for Vitória. We analyzed, in first place, Espírito Saint main roads in the century XIX, through the province presidents' reports. With that, we understood the genesis of the project of transforming Vitória in an important commercial square for the area through the connection of its port with the capixaba and mineiro’s hinterland, the difficulties in the construction and maintenance of the roads of communication of the province and option for the railroad. Soon afterwards, we looked for to understand the meaning and functionality of that means of transportation in the occident, especially, in Europe, North America, South America, discussing the paper of the railroads for their respective savings. We presented, also, the origins and the difficulties of its implantation at national and regional level. We characterized the main areas producing of the province, with the objective of justifying the need of the narrowing of the communications with the most outstanding of them, the South Area. Finally, we narrated the history and the difficulties of construction of the railroad in subject, justifying its internalizing function starting from the narrowing of the economical connection between the capital and the hinterland, tends as parameter the exports of coffee, main source of incomes for the economy of the state.